CURRENT ASPECTS OF FUEL ETHANOL-PRODUCTION IN BRAZIL - Laluce, Cecília [UNESP] (Crc Press Inc, 1991)
Brazil has become a great producer of bioethanol using sugarcane as the basic raw material. Fed-batch process and continuous process are used. Biogas generation from vinasse, production of dry yeast, and autolyzed bagasse for animal feed are making the ethanol production less polluting and more profitable. Bagasse surplus has also been converted into electrical energy. Another alternative use for bioethanol is its conversion to petrochemical derivatives. Up to the present, however, this conversion has been carried out on only a small scale by the industry.
Keywords: ALCOHOLIC FERMENTATION; BIOETHANOL BY-PRODUCTS; FUEL ETHANOL; SACCHAROMYCES-CEREVISIAE